2019
DOI: 10.1111/cpr.12712
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation by mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) can be derived from various adult tissues with multipotent and self-renewal abilities. The characteristics of presenting no major ethical concerns, having low immunogenicity and possessing immune modulation functions make MSCs promising candidates for stem cell therapies. MSCs could promote inflammation when the immune system is underactivated and restrain inflammation when the immune system is overactivated to avoid self-overattack. These cells express many immune suppressors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
351
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 452 publications
(366 citation statements)
references
References 245 publications
(563 reference statements)
2
351
1
12
Order By: Relevance
“…In the past decades, glucocorticoids, cyclophosphamide, calcineurin inhibitors (cyclosporine A and tacrolimus), mycophenolate mofetil, rituximab, tripterygium wilfordii, etc., have been used in the treatment of lupus nephritis and were also mentioned in the KDIGO 2012 guidelines [38]. MSC has been reported to be a good agent for the treatment of some autoimmune diseases in the past decades [3,39,40]. MSC treatment resulted in lower levels of ds-DNA, ANA, Scr, BUN, proteinuria, and renal sclerosis score, and MSC treatment could get a higher level of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, glucocorticoids, cyclophosphamide, calcineurin inhibitors (cyclosporine A and tacrolimus), mycophenolate mofetil, rituximab, tripterygium wilfordii, etc., have been used in the treatment of lupus nephritis and were also mentioned in the KDIGO 2012 guidelines [38]. MSC has been reported to be a good agent for the treatment of some autoimmune diseases in the past decades [3,39,40]. MSC treatment resulted in lower levels of ds-DNA, ANA, Scr, BUN, proteinuria, and renal sclerosis score, and MSC treatment could get a higher level of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are widely investigated because of their therapeutic potentials. In addition to their abilities to differentiate into multiple cell types, they could orchestrate the immune responses and modulate the tissue microenvironment, resulting in tissue regeneration [1][2][3][4][5][6]. Their supportive roles in regulating hematopoietic stem cell (HSC) homeostasis also highlight their therapeutic applications in HSC transplantations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, Ding et al (20) and Park et al (22) found that periodontal stem cells are bene cial for the treatment of a variety of in ammatory and immune diseases. Previous studies have demonstrated that the anti-in ammatory and immunosuppressive effects of MSCs depend on several different pathways, including direct cell contact and secretion of soluble factors (23,24), such as transforming growth factor-β (TGF-β), prostaglandin E2 (PGE2), hepatocyte growth factor (HGF), indoleamine 2, 3-dioxygenase (IDO), nitric oxide (NO), and interleukin-6 (IL-6). PDLSCs can inhibit the proliferation of allogeneic T lymphocytes, which is the result of the combined effect of direct cell contact and secretion of soluble factors (18,21).…”
Section: Introductionmentioning
confidence: 99%